2021
DOI: 10.3390/electronics10202526
|View full text |Cite
|
Sign up to set email alerts
|

A Pentaband Compound Reconfigurable Antenna for 5G and Multi-Standard Sub-6GHz Wireless Applications

Abstract: This work proposes a low-profile, printed antenna that offers pattern and frequency reconfiguration functionalities printed on FR-4 substrate with a size of 46 × 32 × 1.6 mm3. The proposed antenna can operate in five different frequency bands, each one identified as a Mode, wherein there are possibilities of pattern reconfiguration. The frequency and pattern reconfigurability are made possible through 12 p-i-n diode switches (S1 to S12). The former is enabled through the switches S1 to S4 within the radiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The proposed antenna has a size reduction of 90% to other reported antennas like (Pant et al, 2021), (Hussain et al, 2018), (Hussain et al, 2017), (Lim et al, 2012), 84 and 88% of (Lim et al, 2012), (Lee and Jang, 2019) and 48, 56 and 77% of (Ahmad et al, 2021), (Yalavarthi, 2021), (Hassan et al, 2020) respectively. The proposed antenna has a peak gain of 2.8dBi, which is better than (Hussain et al, 2017), (Lim et al, 2012), (Lee and Jang, 2019), (Agrawal et al, 2021), however less than (Pant et al, 2021), (Hussain et al, 2018), (Chen et al, 2019), (Yalavarthi, 2021), (Hassan et al, 2020), (Ahmad et al, 2021). The MIMO antenna achieved minimum isolation of 15 dB and maximum isolation of 21 dB (D-ON) which is better than (Lim et al, 2012), (Yalavarthi, 2021), As a result, it can be concluded that the proposed MIMO antenna has favourable characteristics for use in 5G (sub-6GHz) and WLAN applications.…”
Section: Channel Capacitymentioning
confidence: 77%
“…The proposed antenna has a size reduction of 90% to other reported antennas like (Pant et al, 2021), (Hussain et al, 2018), (Hussain et al, 2017), (Lim et al, 2012), 84 and 88% of (Lim et al, 2012), (Lee and Jang, 2019) and 48, 56 and 77% of (Ahmad et al, 2021), (Yalavarthi, 2021), (Hassan et al, 2020) respectively. The proposed antenna has a peak gain of 2.8dBi, which is better than (Hussain et al, 2017), (Lim et al, 2012), (Lee and Jang, 2019), (Agrawal et al, 2021), however less than (Pant et al, 2021), (Hussain et al, 2018), (Chen et al, 2019), (Yalavarthi, 2021), (Hassan et al, 2020), (Ahmad et al, 2021). The MIMO antenna achieved minimum isolation of 15 dB and maximum isolation of 21 dB (D-ON) which is better than (Lim et al, 2012), (Yalavarthi, 2021), As a result, it can be concluded that the proposed MIMO antenna has favourable characteristics for use in 5G (sub-6GHz) and WLAN applications.…”
Section: Channel Capacitymentioning
confidence: 77%
“…Due to these challenges, the procedure for designing an antenna is revised. To fulfill the requirements of future communication devices, an antenna is required that has characteristics of high gain, high radiation efficiency, omnidirectional radiation pattern, and can operate in over a wideband to enable communications at multiple frequency bands [ 2 , 3 ]. Conformal antennas that can be reconfigurable are considered to fulfill these demanding requirements [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, meta‐surfaces were introduced in various antenna structures as defected ground planes, 3 frequency selective surfaces, 4 and artificial magnetic conductors 5 . Most of these applications were applied to wearable textile WBAN applications, 6 size reduction, 7 antenna gain enhancement, 8 interference isolation, 9 and mutual coupling reduction 10 . Moreover, these artificial structures provided unique features such as distinctive stop bands, 11 surface wave suppressions, 12 and negative effective constitutive parameters 13 …”
Section: Introductionmentioning
confidence: 99%
“…It is good to mention that, in recent 5G networks, two main bands are issued within sub‐6GHz and mm waves (mmW) 10 . Using mmW could realize an excellent reduction in the antenna size and a significant bandwidth enhancement 9 . However, the propagation of mmW inside buildings is very difficult due to the fact of the skin depth and attenuation factors increase with frequency increase 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation